Pseudotype Neutralization Assays: From Laboratory Bench to Data Analysis - Ferrara, Francesca (Methods Protoc, 2018)
Pseudotype neutralization assays are powerful tools to study functional antibody responses against viruses in low biosafety laboratories. However, protocols described in the literature differ widely with respect to material, reagents, and methods used to perform these assays and to analyse the raw data generated. This could result in discrepancies between the results of different laboratories even when the same pseudotypes and the same samples are analysed. Here, we describe, in detail, an experimental protocol to perform pseudotype neutralization assays using lentiviral pseudotypes bearing influenza haemagglutinin and expressing firefly luciferase. We also present the steps necessary to analyse the data and calculate the half maximal inhibitory concentration of the sera analysed. This protocol will provide support for the validation and the standardization of the pseudotype neutralization assay for influenza virus serology. Additionally, it will provide a starting point for the development of pseudotype neutralization assays using pseudotypes bearing other viral envelope proteins.